RELIGIOSITY AND SUSTAINABLE DEVELOPMENT GOALS: DOES IT MATTER? - Riyono , Kenley Maccauley; Widianingsih, Luky Patricia (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Introduction/Main Objectives: This paper explores the impact of religiosity on sustainable development goals across 127 countries. Recently, there has been growing concern about the role of religion in society, as many developed countries have fewer religious followers compared to developing ones. Background Problems: Some evidence suggests that countries with lower levels of religiosity tend to have higher quality of life and a healthier environment. However, religiosity should encourage people to preserve both the social and natural environment. Therefore, it is worth investigating if religiosity serves as a driver for environmental stewardship. Novelty: Previous research has focused on various factors that influence sustainable development goals, but the contribution of religiosity to sustainable development goals has not been extensively examined. Research Methods: This research used multiple linear regression to analyze the current issue, based on religiosity data obtained from CEOWORLD and the Global Business Policy Institute across 127 countries. Finding/Results: Religiosity has a significant negative effect on Sustainable Development Goals. Additionally, GDP was used as a control variable, and the results showed a positive impact on sustainable development goals. Conclusion: The findings of this study provide an implication so that the state in realizing its sustainable development goals together with all its apparatus including religious leaders to have an aligned perspective in executing various programs in realizing the goals of the SDGs.